HIP FRACTURES AND VITAMIN D: A SYSTEMATIC REVIEW - Susilo, Dhanang (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Hip fractures are among the most common types of fractures that patients report with to emergency departments and orthopaedic trauma teams. Study showed association vitamin D and bone intensity. The aim: This article discusses association about hip fractures and vitamin D.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.Result: In the PubMed database, the results of our search brought up 218 articles, whereas the results of our search on SagePub brought up 109 articles. The results of the search conducted for the last year of 2013 yielded a total 88 articles for PubMed and 27 articles for SagePub. In the end, we compiled a total of 32 papers, 23 of which came from PubMed and nine of which came from SagePub. We included seven research that met the criteria.Conclusion: Research consistently shows a link between vitamin D and bone strength. This is related to the incidence of hip fractures.